Knowledge, attitude and implementation of evidence-based practice of physiotherapists in India: A web-based cross-sectional study - Rekha Chaturvedi; Shaveta Khrolia; Vandana Yadav; Meenakshi Bagri; Jyoti (Romanian Journal of Neurology, 2021)
Background and objective. Evidence based practice (EBP) is based on the combination of the best research finding and clinical skill to ease clinical decision-making procedure. Patients treated with evidence-based practices have much better results as compared to the other patients. In today’s world, EBP has attained global acceptance in physiotherapy sector. The objective of the study was to access the knowledge, attitude and implementation of EBP of physiotherapists in India via a cross sectional study. Method. A cross sectional survey was held with the help of a web based customized questionnaire and was sent to physiotherapists. Results. Most of the subjects were affirmative regarding EBP but did not have enough knowledge and expertise for its implementation. The chief barriers for EBP implementation was lack of time and the cost of information resources. Conclusions. Physiotherapists need to upgrade their perspective, knowledge, understanding and skills regarding EBP. Furthermore, EBP must be added to the academic curriculum for its early recognition among the medical students.